20.3k views
0 votes
PLEASE ASAP




.............

PLEASE ASAP .............-example-1
User Fractals
by
5.8k points

1 Answer

1 vote

Answer:


a = \frac{ {v}^(2) - {r}^(2) }{2x}

Step-by-step explanation:


{v}^(2) = {r}^(2) +2 ax

To make a the subject first move r² to the other side of the equation

That's


2ax = {v}^(2) - {r}^(2)

Divide both sides by 2x to make a stand alone

That's


(2ax)/(2x) = \frac{ {v}^(2) - {r}^(2) }{2x}

We have the final answer as


a = \frac{ {v}^(2) - {r}^(2) }{2x}

Hope this helps you

User Zecong Hu
by
4.2k points